Mandibular condyle fracture in Japanese girl and 10-year follow-up findings. Issue 3 (December 2017) - Hamada, Masakazu; Nomura, Ryota; Yano, Hiroyuki; Masui, Atsushi; Kokomoto, Kazuma; Nakano, Kazuhiko; Yura, Yoshiaki
Abstract: A condyle fracture is the most common type of those that occur in the mandible, and is generally treated by an open reduction procedure or conservatively when encountered in children. Conservative treatment often results in a satisfactory long-term outcome of jaw function. Nevertheless, follow-up examinations after treatment are important to minimize potential effects of late complications. An 11-year-old Japanese girl came to us with a fracture of the left-side mandibular condyle. Intermaxillary fixation and Schuchardt splints were initially performed, followed by mouth opening training. Neither trismus nor malocclusion were observed, and the fractured condyle was recovered at 1 year after injury. Additional findings obtained over the 10-year follow-up period are also presented, which indicate the efficacy of conservative treatment of a fracture of the mandibular condyle occurring in children.